(untitled) (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
Street children remain one of Indonesia’s most vulnerable groups, facing violence, exploitation, and limited access to education. This paper documents an individual intervention conducted during a fieldwork placement at a Social Shelter in Medan. Using Charles Zastrow’s six-stage casework method—engagement, assessment, planning, intervention, evaluation, and termination—and guided by Kurt Lewin’s three-stage behaviour-change model (unfreezing, changing, refreezing), the practitioner worked with a child under the age of 18 who had been living on the street for a considerable time and refused schooling. Data were collected through participant observation, in-depth interviews, and internal documentation (assessment records, progress notes, and ecomap). The qualitative, descriptive analysis shows a significant behavioural shift: (1) the client developed awareness of the risks of street life (unfreezing); (2) began practising positive routines such as emotional regulation and study habits (changing); and (3) committed to re-entering formal education while distancing from negative peer groups (refreezing). These findings affirm that a structured casework approach, supported by Lewin’s theory and ecomap-based assessment, can foster sustainable behavioural change in street children.alleviation.